Role of Intra- and Peritumoral Budding in the Interdisciplinary Management of Rectal Cancer Patients. (31st July 2012) - Zlobec, Inti; Borner, Markus; Lugli, Alessandro; Inderbitzin, Daniel
Abstract : The presence of tumor budding (TuB) at the invasive front of rectal cancers is a valuable indicator of tumor aggressiveness. Tumor buds, typically identified as single cells or small tumor cell clusters detached from the main tumor body, are characterized by loss of cell adhesion, increased migratory, and invasion potential and have been referred to as malignant stem cells. The adverse clinical outcome of patients with a high-grade TuB phenotype has consistently been demonstrated. TuB is a category IIB prognostic factor; it has yet to be investigated in the prospective setting. The value of TuB in oncological and pathological practice goes beyond its use as a simple histomorphological marker of tumor aggressiveness. In this paper, we outline three situations in which the assessment of TuB may have direct implications on treatment within the multidisciplinary management of patients with rectal cancer: (a) patients with TNM stage II (i.e., T3/T4, N0) disease potentially benefitting from adjuvant therapy, (b) patients with early submucosally invasive (T1, sm1-sm3) carcinomas at a high risk of nodal positivity and (c) the role of intratumoral budding assessed in preoperative biopsies as a marker for lymph node and distant metastasis thus potentially aiding the identification of patients suitable for neoadjuvant therapy.